Winners and Losers When Private Banks Distribute Government Loans : Evidence from Earmarked Credit in Brazil - Ornelas, Jose Renato Haas; Pedraza, Alvaro; Ruiz-Ortega, Claudia; Silva, Thiago Christiano (World Bank, Washington, DC, 2019)
This paper studies loan conditions in a context where private banks can operate in two credit markets: a free-market with no government intervention and an earmarked market that relies on government funds and where interest rates are regulated. The paper examines the effects of earmarked lending on the spreads of free-market loans using a rich loan-level dataset on all Brazilian firms between 2005 and 2016. The evidence suggests that private banks strategically channel earmarked credit to firms that are ex ante more difficult to lock-in in the free-market– larger firms in more contested regions. The paper highlights a novel channel whereby earmarked credit is used by private banks to extract more rents. Once a firm receives an earmarked credit from its bank, its interest rates on new loans in the free-market increase while the loan volume remains mostly unaffected.